Program Coaching untuk Meningkatkan Personal Growth Initiative Guru SMP dalam Menulis Karya Ilmiah - Dian Juliarti Bantam; Muhammad Erwan Syah (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
Teachers have an important role in education, as facilitators for students to be able to develop their potential interests and talents. One of the skills that need to be mastered by teachers is the ability to write scientific papers, both independently and together with students. The problem is that the written work produced by teachers in Indonesia, in terms of quantity, is still far from that of neighboring countries, including the teachers of SMP Negeri 1 Kalasan. The purpose of this community service is to provide a coaching program to improve personal growth initiatives in writing scientific papers for teachers of SMP Negeri 1 Kalasan. The method used is coaching where the provision of material about motivation to write and writing strategies is followed by coaching training in writing a scientific article. The subjects in this study amounted to 17 teachers at SMK Negeri 1 Kalasan. The time for coaching is 1 day with a duration of 1 hour of material and 3 hours of sincere practice. The result achieved is that all participants write articles on the given google form. The next step is that the participants' writings will be bombed until they are published in the mass media or bulletins.Guru memiliki peran penting dalam pendidikan, sebagai fasilitator bagi siswa untuk dapat mengembangkan potensi minat dan bakat. Salah satu keterampilan yang perlu dikuasai oleh guru adalah kemampuan dalam menulis karya ilmiah, baik secara mandiri maupun bersama-sama dengan siswa. Permasalahnnya karya tulis yang dihasilkan oleh para guru di Indonesia, dari segi kuantitas, masih jauh jumlahnya dengan negara-negara tetangga, tidak terkecuali Guru SMP Negeri 1 Kalasan. Tujuan pengabdian kepada masyarakat ini adalah memberikan program coaching untuk meningkatkan personal growth initiative dalam menulis karya ilmiah pada guru SMP Negeri 1 Kalasan. Metode yang digunakan berupa coaching dimana pemberian materi seputar motivasi untuk menulis dan strategi menulis, kemudian dilanjutkan dengan pelatihan coaching menulis di sebuah artikel ilmiah. Subjek dalam penelitian ini berjumlah 17 orang guru di SM Negeri 1 Kalasan. Waktu pelaksanaan coaching 1 hari dengan durasi pemberian materi 1 jam dan latihan menulus 3 jam. Hasil ang dicapai yaitu semua peserta menulis artikel di google form yang diberikan. Langkah selanjutnya yaitu tulisan peserta yang layak akan di bombing sampai ter publish di media masa atau bulletin.